Phylogenetic Diversity of Koala Retrovirus within a Wild Koala Population - Chappell, K. J. (J Virol, 2017)
Koala populations are in serious decline across many areas of mainland Australia, with infectious disease a contributing factor. Koala retrovirus (KoRV) is a gammaretrovirus present in most wild koala populations and captive colonies. Five subtypes of KoRV (A to E) have been identified based on amino acid sequence divergence in a hypervariable region of the receptor binding domain of the envelope protein. However, analysis of viral genetic diversity has been conducted primarily on KoRV in captive koalas housed in zoos in Japan, the United States, and Germany. Wild koalas within Australia have not been comparably assessed. Here we report a detailed analysis of KoRV genetic diversity in samples collected from 18 wild koalas from southeast Queensland. By employing deep sequencing we identified 108 novel KoRV envelope sequences and determined their phylogenetic diversity. Genetic diversity in KoRV was abundant and fell into three major groups; two comprised the previously identified subtypes A and B, while the third contained the remaining hypervariable region subtypes (C, D, and E) as well as four hypervariable region subtypes that we newly define here (F, G, H, and I). In addition to the ubiquitous presence of KoRV-A, which may represent an exclusively endogenous variant, subtypes B, D, and F were found to be at high prevalence, while subtypes G, H, and I were present in a smaller number of animals. IMPORTANCE Koala retrovirus (KoRV) is thought to be a significant contributor to koala disease and population decline across mainland Australia. This study is the first to determine KoRV subtype prevalence among a wild koala population, and it significantly expands the total number of KoRV sequences available, providing a more precise picture of genetic diversity. This understanding of KoRV subtype prevalence and genetic diversity will be important for conservation efforts attempting to limit the spread of KoRV. Furthermore, KoRV is one of the only retroviruses shown to exist in both endogenous (transmitted vertically to offspring in the germ line DNA) and exogenous (horizontally transmitted between infected individuals) forms, a division of fundamental evolutionary importance.